2014
DOI: 10.1039/c4nj00262h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of a novel class of β-carboline derivatives

Abstract: β-Carboline was modified with amino acids and several novel β-carboline analogues were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Various aromatic β-carbolines has been accessed by oxidative dehydrogenation of their heterocyclic precursors using metal-based reagents. For example selenium dioxide (SeO 2 , 10 equiv) has been used in the presence of an acid for oxidative dehydrogenation of tetrahydro-β-carbolines 49 to afford aromatic β-carbolines 50 ( Scheme 15 ) [ 65 ]. Bhutania et al [ 66 ] has also reported a similar synthesis of 1-aryl-β-carboline derivative 52 starting from 51 ( Scheme 15 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Various aromatic β-carbolines has been accessed by oxidative dehydrogenation of their heterocyclic precursors using metal-based reagents. For example selenium dioxide (SeO 2 , 10 equiv) has been used in the presence of an acid for oxidative dehydrogenation of tetrahydro-β-carbolines 49 to afford aromatic β-carbolines 50 ( Scheme 15 ) [ 65 ]. Bhutania et al [ 66 ] has also reported a similar synthesis of 1-aryl-β-carboline derivative 52 starting from 51 ( Scheme 15 ).…”
Section: Reviewmentioning
confidence: 99%
“… Selenium dioxide and potassium dichromate-mediated oxidative dehydrogenation of tetrahydro-β-carbolines [ 65 66 ]. …”
Section: Reviewmentioning
confidence: 99%
“…This derivative is a potent cytotoxic agent against chronic myeloid leukemia cells (K562) among the series of β-carbolines (Scheme 28). 124 L-Tryptophan (174) has also been used for the preparation of other β-carboline derivatives with different bioactive properties. The β-carboline 185 is prepared from 174 and 4-nitrobenzaldehyde (181) via tandem C-N/C-C bond formation followed by the decarboxylation/oxidation process to produce intermediate 183.…”
Section: Syn Thesismentioning
confidence: 99%
“…12,13 Among the reported properties, it is worth mentioning the potential of β-carboline derivatives as anticancer agents, which has stimulated studies on their synthesis and structure-activity relationship (SAR). [14][15][16][17][18][19][20][21][22][23] These studies revealed that the introduction of appropriate substituents at the 1-, 3-and 9-positions of the β-carboline ring can result in more potent drugs with reduced toxicity and neurotoxic effects.…”
mentioning
confidence: 99%